(untitled) (Ius Novum, 2020)
The ruling that is analysed in the gloss concerns the scope of obligations of a court that lodges a motion with the Supreme Court in accordance with Article 37 CPC to refer a case for hearing to another court of the same instance, and states that the risk to the good of the administration of justice results from the lack of possibilities of conducting a trial before a court having territorial jurisdiction, due to the bad state of health of a party to the proceedings. Providing the justification of the Supreme Court extended by the criteria for referring a case in accordance with Article 37 CPC, the author proves the grounds for the opinion that the discussed requirement must be up-to-date on the date of lodging the motion concerned.